The influence of selected polymers on concrete tightness - current state of knowledge - Krzysztof Powała (Acta Innovations, 2019)
Today’s construction market of materials, contractors and building users, places new demands on individual building materials. Undoubtedly one such material is concrete, which is used in almost all construction projects as a binder for building materials. Therefore, it is necessary that this material is constantly subjected to new tests to find ways to improve its properties. Therefore, many scientists attempt to improve properties such as compressive strength, flexural strength and water resistance. One method is to modify the cement matrix with polymers.